Collaboration Model between Families and Awaliyah Islamic Boarding Schools in Forming Digital Policies for Students Based on Noble Morals - Badrul Helmi; Bahrul Jamil; Lidra Agustina (UKInstitute, 2026)
The digital era presents significant challenges for the character formation of santri in Madrasah Diniyah Awaliyah (MDA), particularly due to unfiltered information flows and limited ethical guidance in online environments. This Community Service (Pengabdian Kepada Masyarakat / PKM) program aimed to develop an integrative collaboration model between families and madrasah to foster digital wisdom grounded in akhlakul karimah. The program employed an educative and collaborative intervention involving teachers, parents, and santri, beginning with problem identification through digital literacy surveys and focus group discussions. The intervention framework was informed by Bronfenbrenner’s ecological systems theory, Islamic moral philosophy derived from the teachings of Luqman al-Hakim, and Lickona’s character education model encompassing moral knowing, moral feeling, and moral action. The results indicate improved ethical awareness, moral decision-making, and self-regulation in santri’s digital behavior, alongside strengthened parental mediation and teacher facilitation. The findings highlight that consistent value alignment between home and madrasah environments is essential for sustainable digital character development. This PKM program demonstrates that faith-based, ecosystem-oriented approaches offer an effective strategy for cultivating digitally literate yet morally grounded students in the digital age.